Formulasi Sediaan Teh Herbal Celup Dari Daun Salam (Eugenia polyantha Wight.) Kombinasi Daun Sirsak (Annona muricata L.) Sebagai Alternatif Anti-Hipertensi - Nirwati Rusli; Siti Hardiyanti Liasambu (STIFA Makassar, 2018)
Bay (Eugenia polyantha Wight.) leaf and soursop (Annona muricata L.) leaf contain flavonoids that have a protective effect on endothelial function as an anti-hypertensive while jasmine flower has a good odor. This study aims to formulate herbal tea bags from bay leaf, soursop leaf, and jasmine flower into tea bag that qualified physical evaluation. The dried leaves of each sample were putted in bag with various concentration then observe the physical characteristics. The result shows that tea bag was qualified according to SNI 01-4324-1996. The water content was 9.46% - 11.94%, total plate count (TPC) however mold and yeast counts (MYC) were 3 x 103 colonies/g and 1 x 104 colonies/g, respectively. However, FA was preferred by the panelists based on its color, odor and taste.